Pengaruh Pelatihan Komunikasi Interpersonal Terhadap Efikasi Diri Sebagai Pelatih pada Mahasiswa - Miftahun Ni'mah Suseno (JIP (Jurnal Intervensi Psikologi), 2009)
This experiment examines the influence of interpersonal communication training in improving self efficacy as a trainer among college students. The hypothesis was that there is a significant difference in self efficacy of a trainer between the experimental and control group. There is also significant difference in self efficacy of a trainer among participants in experimental group between pre and post experiment. The participants of this experiment are college students with age ranging from 21 to 23 years old. The design of this experiment was Pretest Posttest with Control Group Design. A measure of self efficacy was developed by using aspect from Bandura (1997). The training module was developed on the basis ofHardjana Theory (2003). Data were analyzed using gain score method. The result shows that there is a difference in self efficacy of a trainer between experimental and control group (t= 16.989; p<0.01). This means that the interpersonal communication training show influences in increasing self efficacy of a trainer. An experiment group data analysis shows that there is a difference in self efficacy phor and after the training (t= -16.819; p<0.01). The result of this experiment confirmed the hypothesis.Keywords: interpersonal communication, self efficacy, trainer.